EFFECT OF ETHANOLIC FLOWER EXTRACT OF SPATHODEA CAMPANULATA ON STREPTOZOTOCIN INDUCED DIABETIC NEUROPATHY - Bachhav, Rishikesh; Saudagar, Ravindranath (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: To evaluate the effect of ethanolic extract of the flower of Spathodea camapanulata (EFESC) on streptozotocin-induced diabetic neuropathy. Methods: Non-insulin dependent diabetes mellitus (NIDDM) was induced in overnight fasted adult wistar strain albino male rats weighing 160-200g by a single intraperitoneal injection (i. p) of streptozotocin (STZ-65 mg/kg). The rats were randomized into six groups, with six animals each, namely normal control (NC) (Treated with 1% carboxymethyl cellulose solution), diabetic control (DC) (65 mg/kg., i. p. STZ), test group treated at various doses of EFESC250, EFESC500, and EFESC750, standard control-glibenclamide0.25 mg/kg b.w.(SCG) and the treatment has begun from the day of blood sugar level (BSL) detection after the STZ treatment. Body weight was checked daily and serum glucose levels were measured at 48 h, 15th and 28th d of study. Reaction time to thermal hyperalgesia and cold allodynia were measured after induction of diabetes. In vitro, aldose reductase inhibition assay was carried out. Results: The preliminary phytochemical screening revealed the steroids, terpenoids, coumarins, carbohydrates, tannins, glycosides, and flavonoids in EFESC. DC group showed decreased in reaction time (hyperalgesia) compared to NC while a significant increase in reaction time was observed at various doses EFESC250, EFESC500, EFESC750 and SCG0.25. EFESC at various doses showed the significant reduction in BSL and body weight on 15th and 28th d in STZ diabetic rat at various dose levels. In vitro, aldose reductase inhibition was observed with an IC50 at 131 Î¼g/ml. Conclusion: EFESC showed reduced in BSL and prevents hyperalgesia in experimental diabetic neuropathy. It also reduced aldose-reductase level that may play an important role in reducing the complication of diabetic neuropathy.